PS 05-18 CONTINUOUS SYSTOLIC AND DIASTOLIC BLOOD PRESSURE NIGHT-TO-DAY RATIO IN RELATION WITH CORONARY HEART DISEASE AND ISCHEMIC STROKE: A CROSS-SECTIONAL STUDY. (September 2016) - Cai, Anping; Zhou, Yingling; Zhou, Dan; Feng, Yingqing
Abstract : Objective: To evaluate the associations of increased continuous systolic and diastolic blood pressure night-to-day ratio (SBP-NDR and DBP-NDR), indicators of blunted nocturnal BP decline, and composite atherosclerotic cardiovascular diseases (ASCVD) comprising coronary heart disease (CHD) and ischemic stroke (IS). Potential factors associated with increased SBP-NDR and DBP-NDR were also evaluated. Design and Method: A total of 401 consecutive patients who had undergone 24h ambulatory blood pressure monitoring were enrolled. Clinical characteristics were collected and logistic regression analysis was used to evaluate the associations between increased SBP-NDR and DBP-NDR and ASCVD. The relationships between increased SBP-NDP and DBP-NDR and potential factors were assessed by linear regression analysis. Results: In general, subjects (n = 161, 40.1 %) with ASCVD were older (65.1 ± 11.9 years versus 56.0 ± 15.3 years), had higher glycated hemoglobin level, more frequently had a previous diagnosis of hypertension (72.0 % versus 61.3 %) and diabetes (34.8 % versus 15.4 %). Subjects with ASCVD had higher proportions of treatment with anti-platelet agent, statins, anti-hypertensive and glucose-lowering drugs. Logistic regression analysis, after extensively adjusting for potential covariates, showed that increased SBP-NDR and DBP-NDR were significantly associated with ASCVD, with odds ratio (OR) of 1.034 (95% confidence interval (CI) 1.003–1.065, P = 0.031) and OR of 1.030 (95 % CI 1.002–1.059, P = 0.034), respectively. Linear regression analysis showed that advanced age, smoking, CHD and IS were positively associated with increased SBP-NDR and statins was negatively associated with. While only smoking and IS were positively associated with increased DBP-NDR. Conclusions: Increased SBP-NDR and DBP-NDR were comparably associated with ASCVD and differences in factors associated with nocturnal SBP and DBP decline were observed. These findings together suggest that likewise SBP-NDR, DBP-NDR may also be a useful and unique marker of high cardiovascular risk.